Establishment of a Community-Based Mental Health Center in Yazd: A Short Report - Golrasteh Kholasehzadeh; Fatemeh Soryani; Mansureh Nasirain; Mohammad hassan Lotfi (Shahid Sadoughi University of Medical Sciences, 2016)
About 40 years ago, the mental health services providing strategies have been dramatically changed worldwide. As well as, it is considered as a new revolution in mental health and named as community-based mental health movement. Moreover, mental health centers in Iran have been established in order to make a change in urban community-based mental health (CMHC). The first CMHC was founded in Tehran 16th district in 2010. In Yazd, it was established in 2010. In this article, the steps for establishment of the first CMHC were described.